Influence of microstructural evolution on mechanical behavior of Fe-Nb-B ultrafine composites with a correlation to elastic modulus and hardness - Kim, J. T.; Hong, S. H.; Park, H. J.; Park, G. H.; Suh, J. Y.; Park, J. M.; Kim, K. B. (Elsevier BV, 2015)
In this study, we explore the microstructural modulation and mechanical properties of Fe-Nb-B ultrafine composites by the addition of boron. According to the evolution of microstructure, mechanical properties including yield strength and plastic strain were significantly changed. With increase of boron content, Fe-B type compounds were newly formed and eutectic structured matrix was concurrently altered. Newly formed phases with high hardness/elastic modulus leads to considerably increase the yield strength up to 3110 MPa but macroscopic plasticity is deteriorated inadequately. To understand the origin of critically changed macroscopic mechanical properties, the values of hardness and elastic modulus obtained from nanoindentation test were plotted and demonstrated as a contour map. The structural characterization and nano-scale mechanical analysis are capable of providing the clear evidence to understand the relationship between microstructure and mechanical properties of the ultrafine multi-phase composites. (C) 2015 Elsevier B.V. All rights reserved.